Cybersecurity : the essential body of knowledge - Shoemaker, Dan. (Clifton Park, NY : Course Technology, Cengage Learning, 2011)
CYBERSECURITY: THE ESSENTIAL BODY OF KNOWLEDGE provides a comprehensive, trustworthy framework of practices for assuring information security. This book is organized to help readers understand how the various roles and functions within cybersecurity practice can be combined and leveraged to produce a secure organization.
1. The Field of Cyber Security -- 2. The DHS EBK Initiative -- 3. Applying the EBK -- 4. The Executive role -- 5. The Functional role -- 6. The Corollary role -- 7. Data Security -- 8. Digital Forensics -- 9. Enterprise Continuity -- 10. Incident Management -- 11. IT Security Training and Awareness -- 12. IT Systems Operations and Maintenance -- 13. Network and Telecommunications Security -- 14. Personnel Security -- 15. Physical and Environmental Security -- 16. Procurement -- 17. Regulatory and Standards Compliance -- 18. Security Risk Management -- 19. Strategic Security Management -- 20. System and Application Security.
Includes index.
1
Keywords: Data protection; Computer security